Motivation of sex workers who provide camming services to engage in sex with their real-life and virtual partners - Kelberga (Kelberg), Anna; Martinsone, Baiba (Frontiers in Psychology, 2023)
In this study, the motivations of 80 sex workers who provide camming services (76 females and 4 non-binary/trans/gender fluid individuals; aged from 20 to 49 years, M = 30.68, SD = 6.43; 56.2% married or in a committed relationship, 18.8% in a non-committed relationship and 25% - single) were compared in terms of engaging in sexual activity with their real-life partners versus their virtual partners (predominantly kink-oriented clients). Presented with 16 reasons to engage in sexual activity, the respondents rated the frequency to engage in sex for each of these reasons with their real-life and virtual partners. Results showed that there were five reasons in which there were differences in motivation to engage in sex with real-life versus virtual partners and 11 reasons showed no differences. Specifically, respondents reported engaging in sex more often with their virtual partners to get resources and to experience a specific type of sex (kink), while they reported engaging in sex more often with their real-life partners to experience physical pleasure, motivated by physical desirability of a partner and to express love and commitment. However, for all other reasons that motivate people to engage in sex, including stress reduction, experience seeking, self-esteem boost, social status, revenge, utilitarian reasons, emotional expression, duty or pressure, thrill of the forbidden, mate guarding, and desire to have sex with a person of other gender, respondents engaged in sex equally frequently with their real-life and virtual partners (clients) and there were no statistical differences. This study adds to the existing research on sex work by providing insights into the motivations of sex workers to engage in sex with different partners and demonstrates that apart from common sense differences the reasons to engage in sex with clients and real-life partners are vastly similar.